PENERAPAN MODEL PROJECT BASED LEARNING DALAM PEMBELAJARAN TEMATIK TERPADU DI KELAS V SEKOLAH DASAR (STUDI LITERATUR) - Lingga Indra Yani; Taufina Taufik (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This research began with many students who have not been able to complete project tasks to the maximum, students have not been taught in practical activities so that students lack the skills and understanding while learning the project being tested. The Project Based Learning Model is a teaching and learning model that emphasizes student-centered learning on a project that allows students to work independently to achieve their own learning and then reach a peak in results in the form of written works, drawings etc. This research is a literature study that aims to find a picture of the Project Based Learning model in integrated thematic learning in class V of primary schools. In this study, researchers used a literature study, first the researchers formulated the research problem, then proceeded to explore existing research relevant to analysis. Data collection techniques using non-test is by searching electronic journals through Google Sholer. From the research results 15 relevant articles show that the Project Based Learning model is effective in improving student learning outcomes.